HUBUNGAN EMOTIONAL INTELLIGENCE, SELF CONFIDENCE, SELF REGULATED LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS - JL, Ana Risqa; Putri, Aisyah Sabila; Netriwati, Netriwati (JURNAL LEMMA, 2024)
This research aims to analyze the relationship between emotional intelligence, self-confidence and self-regulated learning on students' mathematical reasoning abilities. Mathematical reasoning is an important ability that needs to be developed in learning mathematics. This research uses a quantitative approach with correlational methods. The independent variables in this research are emotional intelligence, self-confidence, and learning independence, while the dependent variable is mathematical reasoning ability. Data collection was carried out through questionnaires to measure the variables emotional intelligence, self-confidence, and self-regulated learning, as well as mathematical reasoning ability tests. Data analysis uses multiple regression statistical techniques to test the relationship between variables. It is hoped that the research results will provide insight into the role of psychological factors in developing students' mathematical reasoning abilities, as well as being a consideration in designing more effective mathematics learning strategies.